La glose comme outil de désambiguïsation référentielle des noms propres purs - Montserrat Rangel Vicente (Corela)
All proper nouns are potentially multireferential given that they are associated to their referent by extralinguistic links and not in a lexical sence, which would characterise the type of referent to which it is susceptible to be applied to. Consequently, in the writing text there is only the textual context as a means of removing all referential ambiguity from the proper noun. My research hinges on automatic language processing and praxematic linguistics. As such, I will attempt to develop computational grammar from a structure that I will call glose and which, within the framework of nominal semantics, turns out to be a privileged tool for clarifying the proper noun's referential ambiguity. The corpus used for this study will essentially be composed of on line Spanish journalistic texts.